ANALISIS SEKTOR UNGGULAN DALAM PEMBANGUNAN WILAYAH KABUPATEN KUDUS TAHUN 2017-2021 - Anita Magfiroh; Alif Fikri; Rena Uli Farista (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
Selection and priority planning with the consideration that the leading sector can determine the increase in the income of a region and encourage the increase of other sectors which will ultimately improve the regional economy. This study aims to determine the leading sectors in Kudus Regency in increasing regional economic development. The approach used is an approach using analysis tools Location Quotient (LQ), Shift-Share(SS), and Klassen Typologi. The data used is Gross Domestic Product (GDRP) of Kudus Regency and Central Java Province in 2017-2021 and the total of population of Kudus Regency. The results showed that: 1) The basic sector in Kudus Regency is The Manufacturing Sector with an LQ value 2,31. 2)Of the 17 economic sectors, there are 7 sectors that have a competitive advantage with a positive SS value. 3) The results of the Klassen Typology anlysis show that there are no sectors into quadrant I or sectors that are developed and growing rapidly.